Study of the efficacy of trauma and injury severity score to predict survival in patients of polytrauma - Singh, Anant; Chejara, Raj K.; Sharma, Ashok K.; Tolat, Aditya (International Surgery Journal, 2021)
Background: Trauma is one of the major cause of mortality and morbidity in both developed and developing countries. Polytrauma patients present particular challenges as profile of the patient varies with different types and severity of injuries. Prediction of survival in trauma patients is an essential requirement of trauma care. Trauma and injury severity score (TRISS) have been considered as a standard of the quality of trauma care. Study was carried out to evaluate the performance of TRISS in predicting survival in patients of polytrauma. Methods: Prospective observational study was conducted in emergency department of a tertiary care centre. 100 patients were evaluated in the study for a period of 18 months between November 2019 and April 2021. Patient demographics, details of trauma, pattern of injuries and physiological status were recorded. Overall outcome were studied and data analysis was done on the basis of TRISS. Statistical analysis was performed using statistical package for the social sciences (SPSS) program for windows, version 25.0 (SPSS Chicago, Illinois). Results: Young patients with mean age of 34.54 were most commonly affected in polytrauma with male preponderance. Road traffic accidents were the most common mode of trauma followed by fall from height. Blunt trauma was the most common type of injury. TRISS strongly predicted survival in polytrauma patients (AUC 0.926 CI 95% 0.868-0.985). TRISS has high sensitivity 97.62% and specificity 62.50% at a cut off of 64.50%. Conclusions: TRISS is an effective method for predicting survival of polytrauma patients and thus can be utilized to evaluate and compare trauma care.